Imagining Education: An Arendtian Response to an Inmate’s Question - Meyer, Karen Ann; Fels, Lynn (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
This article responds to a what if question regarding education raised by a woman inmate. Emerging in the midst of a research project with women in prison, the unexpected question haunts the two authors, both educational researchers, who in turn reconsider education’s role in difficult circumstances. For guidance, the authors turn to Hannah Arendt’s concept of natality as the capacity to renew, and Natasha Levinson’s claim that its preservation is critical to education. The authors examine the gap between past and future as a potential space to imagine education otherwise, both within the project and the larger perspective of education.